The Urgency of Halal Certification According to Gen Z as Business Actors and Consumers in Viral Culinary: Case Study in Pamekasan City - Diah Utami; Ah. Kusairi (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
The culinary trend that spreads through social media is apparently not a mild phenomenon. He reshaped the way Gen Z consumes food as well as the way they see business opportunities and in it, questions about the halalness of products began to be carried away. This research is also here to answer one thing that has gone unnoticed seriously: how urgent halal certification really is in the eyes of Gen Z, both those who are pioneering the culinary business and those who become consumers every day, in the midst of the viral culinary frenzy of Pamekasan City. This research does not stop at the conceptual level. The choice of empirical legal methods with case studies is not without reason This approach allows researchers to really hear the voice of the perpetrator in the field, rather than just fumbling from afar. In-depth interviews and direct observations were conducted on business actors and Gen Z consumers whose lives have indeed been integrated with the digital culinary ecosystem. And from there, one thing becomes clear: halal certification is seen not as a complement, but as a pillar. It is considered important to protect consumers, build trust, and provide a strong legal basis for culinary businesses in the midst of rapidly changing trends. But the reality on the ground is not always in line with expectations. Awareness exists, but the execution is stuck. The understanding of halal is still shallow in many circles, certification is often considered an administrative matter that can be set aside, and the management process itself still feels burdensome for MSME actors whose resources are limited. What's even more surprising is that Gen Z consumers of the supposedly critical generation often buy without asking. Interesting content on the screen moves their hands faster than information about the halalness of the product. Ultimately, this research carries a broader message than just the matter of labels on the packaging. Halal touches on social aspects, has economic weight, and holds real strategic value for the sustainability of modern culinary businesses. Theoretically, this study enriches the understanding of the halal lifestyle of Gen Z through the lens of the Theory of Planned Behavior, a framework that has been used more often in other contexts. In practical terms, the recommendations are clear and urgent: strengthen halal literacy from the roots, and simplify the certification process so that it is no longer a barrier for growing culinary MSMEs.